The Influence of Leadership Style and Supervision by School Principals on the Performance of Public High School Teachers in Baturaja Timur Sub-District, OKU District - Indah Pagiriani; Munajat, Munajat; Yetty Oktarina; Achmad Tarmizi (Jurnal Ekonomi, 2024)
The purpose of this study was to analyze the effect of leadership style and supervision by the principal on the performance of public high school teachers in East Baturaja District, OKU Regency, using quantitative methods where the research results are presented in descriptive form using statistical figures. The independent variables in this study are leadership style (X1) and principal supervision (X2) while teacher performance (Y) is the dependent variable. From the results of data analysis, it can be proven that the principal's leadership is very influential on teacher performance. The magnitude of this influence is expressed by the coefficient of determination of 99%. This is understood because leadership has a very important role in moving the wheels of the organization so as to improve the quality of teacher work. With the regression equation Y = 2.610 + 1.437 X1 shows that each increase of one unit of principal leadership score will cause an increase in teacher performance score by 1.437 units at a constant 2.610. The magnitude of the influence of supervision is expressed by the coefficient of determination of 88%. Academic supervision carried out by principals has a very important function for teachers in improving their performance in relation to their main duties and functions. Based on the results of multiple regression obtained from the analysis of the table, R square is 98.7 which is the square of 0.9942 This score is the coefficient of determination which is the coefficient of determination.